Systems thinking for assistive technology: a commentary on the GREAT summit - MacLachlan, Malcolm; Scherer, Marcia J (Disability and rehabilitation. Assistive technology, 2018)
The area of assistive technology has a long history of technological ingenuity and innovation. In order to ensure that the benefits of assistive technology are equitably distributed across the population and life course, it is necessary to adopt a systemic approach to the area. We describe examples of systems thinking and non-systems thinking across 10 Ps. These Ps are People (or users, as the primary beneficiaries of assistive technology), Policy, Products, Personnel, Provision (as key strategic drivers at systems level); and Procurement, Place, Pace, Promotion and Partnership (as key situational factors for systems). Together these Ps should constitute a framework for an "open" system that can evolve and adapt, that empowers users, inter-connects key components and locates these in the reality of differing contexts. The adoption of a stronger systems thinking perspective within the assistive technology field should allow for more equitable, more resilient and more sustainable assistive technology across high, middle- and low-income contexts and countries. Implications for Rehabilitation The progress of assistive technology provison has been hampered by disconnected initiatives and activities and this needs to be corrected. Systems thinking is a way of thinking about the connections between things and how these are influenced by contextual and other factors. By encouraging the providers and users of assitive technology to think more systemically we can provide a more cohesive and resilient systems. The user experience is the central component of systems thinking in assistive technologies.
Keywords: sustainable development goal; design vybavení; marketing zdravotnických služeb; postižení; systémová integrace; systems thinking; Research; Equipment Design; Orthopedic Equipment; user involvement; Persons with Disabilities; postup; Marketing of Health Services; Assistive technology; Humans; ortopedické vybavení; Policy; výzkum; pomůcky pro sebeobsluhu; Self-Help Devices; Systems Integration; lidé